2016
DOI: 10.1016/j.paid.2016.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Trait anxiety predicts the emotional valence of meaning-making in life stories: A 10-year prospective study

Abstract: Individuals interpret events in positive and negative ways, creating positive and negative meaning in their life stories. We hypothesized that higher trait anxiety measured 10 years earlier would predict more negative meaning-making in life stories and that negative meaning-making would be related to more concurrent depressive symptoms. Participants were 272 women who

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Consistent with previous studies, it was found that positive emotional tone and positive selfevent connections were related to greater subjective well-being, especially for past chapters (Adler et al, 2016;Banks & Salmon, 2013;Lilgendahl & McAdams, 2011;Lilgendahl, McLean & Mansfield, 2013;McAdams et al, 2001;Thomsen et al, 2016).…”
Section: Narrative Identity and Subjective Well-beingsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies, it was found that positive emotional tone and positive selfevent connections were related to greater subjective well-being, especially for past chapters (Adler et al, 2016;Banks & Salmon, 2013;Lilgendahl & McAdams, 2011;Lilgendahl, McLean & Mansfield, 2013;McAdams et al, 2001;Thomsen et al, 2016).…”
Section: Narrative Identity and Subjective Well-beingsupporting
confidence: 90%
“…A definitive version was subsequently published in Memory, 26, 219-228. DOI:10.1080/09658211.2017.1344250 Lilgendahl, McLean & Mansfield, 2013McAdams, Reynolds, Lewis, Patten, & Bowman, 2001;Thomsen, Matthiesen, Frederiksen, Ingerslev, Zachariae, & Mehlsen, 2016). While these studies mostly use correlational design, some experimental studies suggest that the ways individuals recall and narrate identity-defining events may influence well-being, although more studies are needed before firm conclusions can be drawn (e.g., Cili & Stopa, 2014;Jennings & McLean, 2013).…”
Section: Narrative Identity and Well-beingmentioning
confidence: 99%
“…I became more confident in myself.” Such causal connections support coherence and meaning in life stories (Habermas & Bluck, ). Importantly, the causal connections constructed through autobiographical reasoning are not always positive, sometimes individuals draw negative conclusions about themselves, as exemplified here “I convinced myself and felt sure that I was a dispensable thing… that no one noticed me or protected me… I felt unimportant and it became worse and resulted in bad self‐esteem” (Banks & Salmon, ; Lilgendahl & McAdams, ; Thomsen, Matthiesen, Frederiksen, Ingerslev, Zachariae & Mehlsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with past research on narrative meaning (e.g., Lilgendahl & McAdams, 2011;McLean & Pratt, 2006;Merrill et al, 2016) but adding new texture to this line of research, our findings show that defining the self as positive at the life story level is associated with meaning-making that ultimately is related to self-esteem. Specifically, our finding relating positive meaning-making to selfesteem articulates direct and mediating roles for positive meaning-making particularly to support self-esteem, and in a 1-year longitudinal context (see also Pals, 2006;Thomsen et al, 2016). The mediating role speaks to the relative importance of the narrator's personality and the process of narration: It is the process of making positive meaning when talking about important life events that is responsible for higher self-esteem.…”
Section: Positive Meaning-making As a Pathwaymentioning
confidence: 60%
“…She thereby highlights, as we hope to do, memory processes as a critical impetus that connects basic personality tendencies with adaptive outcomes. In a longitudinal study, Thomsen et al (2016) found that negative meaning-making in life stories explains the relation between trait anxiety and depressive symptoms 10 years later. In line with their research, we suggest in the current study that individuals who have a more positive personality are likely to narrate more positive meaning when describing self-defining events, and use memories to serve adaptive psychosocial functions, leading to an adaptive outcome (i.e., self-esteem).…”
Section: Two Social-cognitive Processes: Positive Meaning-making and mentioning
confidence: 99%